Bequest Motives: A Comparison of Sweden and the United States - John Laitner; Henry Ohlsson (Uppsala University, Department of Economics, 1998)
This paper reviews four well-known theoretical models of private bequest behavior, notes their differing implications for public policy, and discusses a way of empirically discriminating among them. Then it implements the test with micro data from Sweden (LLS) and the U.S. (PSID). The so-called altruistic (or dynastic) model, which, among the four models, has perhaps the most wide-ranging implications for policy, receives some, though limited, support in the LLS, but not the PSID. The inter-country difference is statistically significant. There is evidence of a potential complication due to a dependence of children's education on parents financial status in the case of the U.S.
urn:nbn:se:uu:diva-2423
Keywords: D64; D91; 330; accidental model; altruistic model; egoistic model; exchange model